Genome-wide profiling of WRKY genes involved in flavonoid biosynthesis in Erigeron breviscapus - Song, Wanling; Zhang, Shuangyan; Li, Qi; Xiang, Guisheng; Zhao, Yan; Wei, Fan; Zhang, Guanghui; Yang, Shengchao; Hao, Bing (Frontiers in Plant Science, 2024)
The transcription factors of WRKY genes play essential roles in plant growth, stress responses, and metabolite biosynthesis. Erigeron breviscapus, a traditional Chinese herb, is abundant in flavonoids and has been used for centuries to treat cardiovascular and cerebrovascular diseases.However, the WRKY transcription factors that regulate flavonoid biosynthesis in E. breviscapus remain unknown. In this study, a total of 75 EbWRKY transcription factors were predicted through comprehensive genome-wide characterization of E. breviscapus and the chromosomal localization of each EbWRKY gene was investigated. RNA sequencing revealed transient responses of 74 predicted EbWRKY genes to exogenous abscisic acid (ABA), salicylic acid (SA), and gibberellin 3 (GA3) after 4 h of treatment. In contrast, the expression of key structural genes involved in flavonoid biosynthesis increased after 4 h in GA3 treatment.However, the content of flavonoid metabolites in leaves significantly increased at 12 h. The qRT-PCR results showed that the expression patterns of EbWRKY11, EbWRKY30, EbWRKY31, EbWRKY36, and EbWRKY44 transcription factors exhibited a high degree of similarity to the 11 structural genes involved in flavonoid biosynthesis. Protein-DNA interactions were performed between the key genes involved in scutellarin biosynthesis and candidate WRKYs.The result showed that F7GAT interacts with EbWRKY11, EbWRKY36, and EbWRKY44, while EbF6H has a self-activation function. This study provides comprehensive information on the regulatory control network of flavonoid accumulation mechanisms, offering valuable insights for breeding E. breviscapus varieties with enhanced scutellarin content.